Characteristics of male perpetrators of intimate partner violence and implications for women's HIV status: A pooled analysis of cohabiting couples from 27 countries in Africa (2000-2020). - Salome Kuchukhidze; Dimitra Panagiotoglou; Marie-Claude Boily; Souleymane Diabaté; Jeffrey W Imai-Eaton; Heidi Stöckl; Francisco Mbofana; Rhoda K Wanyenze; Mathieu Maheu-Giroux (Public Library of Science (PLoS), 2023)
Intimate partner violence (IPV) may increase women's HIV acquisition risk. Still, knowledge on pathways through which IPV exacerbates HIV burden is emerging. We examined the individual and partnership-level characteristics of male perpetrators of physical and/or sexual IPV and considered their implications for women's HIV status. We pooled individual-level data from nationally representative, cross-sectional surveys in 27 countries in Africa (2000-2020) with information on past-year physical and/or sexual IPV and HIV serology among cohabiting couples (≥15 years). Current partners of women experiencing past-year IPV were assumed to be IPV perpetrators. We used Poisson regression, based on Generalized Estimating Equations, to estimate prevalence ratios (PR) for male partner and partnership-level factors associated with perpetration of IPV, and men's HIV status. We used marginal standardization to estimate the adjusted risk differences (aRD) quantifying the incremental effect of IPV on women's risk of living with HIV, beyond the risk from their partners' HIV status. Models were adjusted for survey fixed effects and potential confounders. In the 48 surveys available from 27 countries (N = 111,659 couples), one-fifth of women reported that their partner had perpetrated IPV in the past year. Men who perpetrated IPV were more likely to be living with HIV (aPR = 1.09; 95%CI: 1.01-1.16). The aRD for living with HIV among women aged 15-24 whose partners were HIV seropositive and perpetrated past-year IPV was 30% (95%CI: 26%-35%), compared to women whose partners were HIV seronegative and did not perpetrate IPV. Compared to the same group, aRD among women whose partner was HIV seropositive without perpetrating IPV was 27% (95%CI: 23%-30%). Men who perpetrated IPV are more likely to be living with HIV. IPV is associated with a slight increase in young women's risk of living with HIV beyond the risk of having an HIV seropositive partner, which suggests the mutually reinforcing effects of HIV/IPV.